“Working with little:” Access to market infrastructure and its effect on food handling and food safety among vegetable traders in an African city - Kushitor, Sandra Boatemaa; Badu, Mercy; Kushitor, Mawuli Komla; Currie, Paul (Frontiers in Sustainable Food Systems, 2022)
Despite the crucial role played by informal markets in food distribution globally, the sector is ignored and marginalized. This study examined vegetable traders, the trading infrastructure available to them in the market, and how they conduct their businesses to explain the high food safety challenges in the sector. This paper is based on a survey, a learning journey, and transformation labs with market traders in Kumasi, Ghana. The study revealed that most traders were self-employed women with low education who worked for long hours. Access to electricity, water, refrigerators, and storage facilities was limited in the market. Vegetable spoilage was the highest cost associated with their trade. Due to the high spoilage rate, the traders sold the best vegetables at high prices and sold the bruised and rotten vegetables to local eateries and animal farms. The women made no losses through these strategies but used unsafe food handling practices and highly-priced wholesome vegetables. Their actions can reduce urban food security, especially in low-income households. Access to market infrastructure was influenced by availability, power and cost. Vegetable trading was the predominant livelihood of the traders. To improve the efficiency of the sector, efforts can be made toward the provision of services at the markets, and advocacy of the traders about food security implications of their actions by the municipal assemblies and market leaders.